2021
DOI: 10.48083/hxbk3263
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Metabolic Abnormalities in Pakistani Children With Renal Stones

Abstract: Objective: To determine the frequency of various metabolic abnormalities in children with urinary lithiasis. Methods: This cross-sectional study was conducted at the Armed Forces Institute of Urology, Rawalpindi, from 30 January 2017 to 1 February 2020. A total of 1355 children who were aged 4 to 14 years and who had renal stones were included, while those with urinary tract infections, posterior urethral valve, pelvi-ureteric junction obstruction, reflux disease, and chronic renal failure were excluded. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other metabolic abnormalities included hypocitraturia (31%), hyperoxaluria (18%), and hyperuricosuria (11.65%). 19 The incidence of metabolic abnormalities in children with urinary lithiasis was the subject of a study at the AFIU Rawalpindi. The study found that 22.8% of the children had metabolic abnormalities, with the most common abnormality being hypocitraturia (59.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other metabolic abnormalities included hypocitraturia (31%), hyperoxaluria (18%), and hyperuricosuria (11.65%). 19 The incidence of metabolic abnormalities in children with urinary lithiasis was the subject of a study at the AFIU Rawalpindi. The study found that 22.8% of the children had metabolic abnormalities, with the most common abnormality being hypocitraturia (59.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The most common anomaly found was hypocitraturia, which was followed by hypercalciuria and hypomagnesuria. 11 The purpose of the current study is to determine how frequently children in developing countries like Pakistan with urolithiasis have metabolic abnormalities alongwith clinical features. This is meant to assist doctors in creating management protocols that include urine metabolic tests as a key component in an effort to stop stone recurrence.…”
Section: Introductionmentioning
confidence: 99%